Rabbaniah Sources Of Knowledge Vs Insaniah Sources Of Knowledge:scenario Of Islamic Education Teachers In Secondary School In Malaysia - Nurul Asiah Fasehah Muhamad; Mahyuddin Hashim; Noornajihan Ja‘afar; Norzulaili Mohd Ghazali; Syed Najihuddin Syed Hassan; Robiatul Adawiyah Ahmad; Nurul Wahidah Fauzi; Muhammad Widus Sempo (AENSI Publications, 2024)
The source of knowledge is a matter of great importance in determining a reference set of knowledge by Muslims or otherwise, especially when it involves Islamic Education teachers (IEt). IEt is entrusted with a very important responsibility to produce content individual students wordly and hereafter, also well-balanced physically, emotionally, spiritually and intellectually. The source of knowledge that is being referred to by the IEt will decide on the teaching practice that will be displayed in class and will be the supporting environmental factor in moulding the self-concept of the students, whether it fulfils the vision and objective of the Islamic Education Philosophy or National Education Philosophy and vice-versa. Thus, the objective of this research are: 1) To analyse the level of IETs’ belief on Rabbaniah source of knowledge and; 2) To inculcate the level of IETs’ belief on insaniah source of knowledge. The research paper uses quantitative data as the primary data and supported with qualitative data to enrich its data. The quantitative data is analysed descriptively using SPSS 2.0. The study found that IEt mainly refer to human (insaniah) resources rather than Rabbaniah resources. The result gives implication towards Ministry of Malaysian Education, Institution of teacher education and IETs.